2021
DOI: 10.1021/acssuschemeng.1c06960
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Phytochemical Basis and the Mechanism of Plant Extract-Mediated Eco-Friendly Synthesis of Silver Nanoparticles Using Ultra-Performance Liquid Chromatography Coupled with a Photodiode Array and High-Resolution Mass Spectrometry

Abstract: Plant extract is a complex concoction of several phytochemicals, for instance, phenolics, sugars, flavonoids, xanthones, and several others. In general, it is said that hydroxyl-rich phenolics act as reducing agents for metal ions, but little is discussed about the stabilizing ligands of metal nanoparticles (NPs). Thus, despite the popularity of plant extract-mediated synthesis of NPs, the phytochemical basis of the process and the exact mechanism are still unclear. Herein, a systematic study was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 47 publications
(69 reference statements)
3
30
0
Order By: Relevance
“…A previous study on the green synthesis of silver nanoparticles has proved that the phytochemicals such as phenolic acids and flavonoids present in the plant extract act as the reducing agents and the phytochemicals such as the xanthones and phloroglucinols act as the capping agents, and another compound, naphthodianthrones are involved in both the steps. 42 This also proves our claim of the role of the phytochemicals in the synthesis of the BdkR-AgNPs. 42 , 43 Through visual assessment of the reaction mix (reaction solution) in terms of the shift of the pigment to brown color, the BdkR-Ag nanoparticle synthesis was confirmed ( Figure 1B ).…”
Section: Resultssupporting
confidence: 76%
“…A previous study on the green synthesis of silver nanoparticles has proved that the phytochemicals such as phenolic acids and flavonoids present in the plant extract act as the reducing agents and the phytochemicals such as the xanthones and phloroglucinols act as the capping agents, and another compound, naphthodianthrones are involved in both the steps. 42 This also proves our claim of the role of the phytochemicals in the synthesis of the BdkR-AgNPs. 42 , 43 Through visual assessment of the reaction mix (reaction solution) in terms of the shift of the pigment to brown color, the BdkR-Ag nanoparticle synthesis was confirmed ( Figure 1B ).…”
Section: Resultssupporting
confidence: 76%
“…It is believed that the phloroglucinols (hyperforin, Adhyperforin), the naphthodianthrone hypericin, the flavonoids (rutin, quercetin, quercitrin, quercitrin-hydrate, hyperoside), the bioflavonoid biapigenin, and the phenolic acid chlorogenic acid identified previously in the aqueous St John’s wort extract [ 46 ] played a role in the silver reduction and that the stabilization of the formed nanoelement might endow the AgNPs with advantageous bioactivities, such as antibacterial, antioxidant, and anti-cancer activity. Such an assumption is reinforced by the finding of Pradeep et al [ 45 ], where the polar fraction containing phenolic acids and flavonoids was involved in the reduction of Ag+ ions, while the lower polar one containing biflavonoids, phloroglucinols, and naphthodianthrones acted as a capping agent. Moreover, in the same context, the presence of hypericin, pseudohypericin, hyperforin, and flavonoids in H. perforatum extracts and low polar compounds on the surface of NPs contributes to their antioxidant and antibacterial activities [ 39 , 40 , 41 , 57 ].…”
Section: Resultsmentioning
confidence: 96%
“…Several studies highlighted the role of H. perforatum aqueous extract in the reduction of metal ions to nanoelements and in stabilizing the biogenic particles. Its extract was used in reducing gold (III) chloride hydrate (HAuCl 4 ) and silver nitrate (AgNO 3 ) to AuNPs with antidepressant and antioxidant activity [ 43 , 44 ], and AgNPs with antibacterial, antioxidant, and anticancer activities [ 4 , 41 , 42 , 45 ]. Therefore, the present study aimed to investigate the role of AgNPs capped with H. perforatum ’s metabolites in controlling bacterial growth and wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The reducing potential of different classes of plant secondary metabolites to synthesize nanoparticles has been excellently reviewed [ 46 , 47 ]. Biomolecules with various structural classes, such as phenolics, flavonoids, terpenoids, saponins, alkaloids, etc., that are present in plant extracts may be involved as reducing and stabilizing agents in nanoparticles synthesis; however, complexity regarding the exact mechanism of synthesis exists [ 48 , 49 ]. Notwithstanding, the complex nature of plant extracts, the synergism of metabolites in reducing metal ions and differential phytochemical profiles of plant species may be the factors that contribute to uncertainty regarding a generalized mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the complex nature of plant extracts, the synergism of metabolites in reducing metal ions and differential phytochemical profiles of plant species may be the factors that contribute to uncertainty regarding a generalized mechanism. A recent study conducted by Pradeep et al [ 48 ] demonstrated that compounds such as kaempferol-3-glucoside, quercetin and quercetin-3-glucoside are able to reduce silver ion sizes. The same study showed that metabolites with enol groups reduce metal ions to nanoparticles due to their antioxidant potential and metabolites with methoxy groups act as capping agents.…”
Section: Discussionmentioning
confidence: 99%